Zasady prawa w świetle materiałów legislacyjnych - Bielska-Brodziak, Agnieszka; Tkacz, Sławomir (Filozofia Publiczna i Edukacja Demokratyczna, 2018)
The paper discusses the possibilities for using legislative materials in the process of establishing a catalogue of legal principles and determining their content. The starting point for the analysis was the conviction that the catalogue of legal principles and their content are established through discourse. One element of this discourse is the legislator’s voice in the form of „traces” left in various places. The interpreter may refer to both the legislator’s expressions in texts of normative acts and to expressions presented in legislative materials. Until recently, given their insufficient availability, legislative materials were seldom used in the discourse on legal principles. Through an analysis of legislative materials developed for the 2016 amendment of the Code of Criminal Proceedings, the authors show that these materials can be a source of valuable information on the legislative intent. The paper concludes with the following observation: the currently available access opportunities offered by information technologies mean that expanding the context that shapes the catalogue and content of the various principles through the use of legislative materials appears necessary.